Toward a revision of the bamboo corals: Part 6, Illuminating a new candelabrum genus (Octocorallia: Keratoisididae) - France, Scott C.; Watling, Les (Zootaxa, 2024)
Observations and collections made using remotely operated vehicles (ROV) outfit with high-definition video cameras on bathyal seamounts of the North Atlantic and North Pacific have revealed a bamboo coral (Octocorallia, Keratoisididae) with consistent and recognizable colony morphology: a long unbranched “stem” from which many vertically aligned branches arise in a single plane to produce the aspect of a tall candelabrum. Additional observations encountered colonies with only 3 branches arising from the central terminal node to produce the appearance of a standing trident. Genetic analyses suggested both colony morphologies (trident and candelabrum) to be the same species at different growth stages. Herein we formally describe this taxon, Tridentisis candelabrum n. gen. n. sp., erecting a new genus to accommodate the unique and distinctive colony morphology, and discuss morphological variation observed across the documented geographic range.